The North Carolina Colony - Fradin, Dennis B. (Chicago : Childrens Press, 1991)
Traces the history and people of the colonial period in North Carolina.
Includes index.
Keywords: North Carolina -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; North Carolina -- History -- Colonial period, ca. 1600-1775.